Analysis of the Framing Model of Zhongdang Pan and Gerald M. Kosicki in Reporting on the Moving of the National Capital in Online MediaTempodot.co - Rizky Pratama; M. Yoserizal Saragih (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The purpose of this research is to find out the analysis of Tempo.co's online media framing regarding the translocation of The New Capital for the period of January 2022. In answering these problems, the author uses a constructivist approach, namely an analysis that sees discourse as a result of the construction of social reality. This research is classified as library research, data is collected by citing and analyzing using framing analysis with representative literature and having relevance to the problems discussed, then reviewing and concluding. After discussing the framing analysis regarding the relocation of the National Capital using the Zhongdang Pan and Gerald framing method. M. Kosicki. The author found that, from the framing device side (Syntax, Script, Thematic and Rhetorical), Tempo.co showed that in constructing social reality, especially news about the relocation of the State Capital, it was quite neutral in presenting the news according to the information obtained from sources.